PHYSICAL EDUCATION STUDENTS OF THE PERSPECTIVE OF YOUTH AND ADULTS IN THE MUNICIPALITY OF RIO POMBA-MG (Fiep Bulletin - online, 2013)
The Education of Youth and Adults is a teaching method designed for those who have not completed in regular time, the Elementary and Secondary Education. The Youth and Adult encompasses an audience of varying ages, bringing together different lifestyles: religion, culture and knowledge, thus forming a very heterogeneous group of people who are in search of new knowledge. Objective: Having the discipline of physical education as mandatory, optional on the other hand most students of the night class, where the Education of Youth and Adults, this study aims to find out if students are aware of this support and how they behave in front of classes taught teachers, such as teacher-student relationship by describing the students. Methodology: The study included 101 students of Education Youth and Adult education elementary and middle schools in two of the city of Rio Pomba / MG. Participants answered a semi-structured questionnaire with ten questions. The percentile analysis was employed to verify the data. Conclusion: Students believe in the obligation and the importance of Physical Education for training them. There is also a preference for classes where you have to practice and theory, the more they say the practice is prevalent in physical education classes. The content is worked over the sport. On participation in physical education classes, most attend classes. Of those who answered no, there is reason most often cited as the tiredness. The classes and teachers were evaluated by students as "good." There should be more studies to enable future professionals indicative and allowances for a practice consistent with the main issues that students are seeking / experiencing.
Keywords: Physical Education; Youth and Adult Education (EJA); Vision of the students